2020
DOI: 10.3390/su12114682
|View full text |Cite
|
Sign up to set email alerts
|

Urban Sustainability and Smartness Understanding (USSU)—Identifying Influencing Factors: A Systematic Review

Abstract: Urban Sustainability and Smartness Understanding (USSU) can be defined by a group of sociopsychological determinants (such as awareness, perception, attitude and behavior) which shapes the relationship between human beings and the environment in which they live. A variety of influencing factors must exist in relation to USSU, however, a comprehensive examination of these, looking at personal, social, environmental, economic, technical, and governance perspectives in an urban context, appear to be less well res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 60 publications
(325 reference statements)
0
12
0
Order By: Relevance
“…Although it is not fully possible to comprehend the entire list of external factors, several studies would give some intuition [12] and, therefore, it is possible to embed a preliminary set of factors within our model. For example, Topal et al [93] proposed a theoretical framework about urban sustainability understanding, which consists of a wide range of influencing factors grouped under six main and 15 secondary broad categories [93]. For more in-depth examination, this framework could be considered.…”
Section: Influential External Factors (Situational/contextual)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is not fully possible to comprehend the entire list of external factors, several studies would give some intuition [12] and, therefore, it is possible to embed a preliminary set of factors within our model. For example, Topal et al [93] proposed a theoretical framework about urban sustainability understanding, which consists of a wide range of influencing factors grouped under six main and 15 secondary broad categories [93]. For more in-depth examination, this framework could be considered.…”
Section: Influential External Factors (Situational/contextual)mentioning
confidence: 99%
“…(1) Demographics are found to have a varying but prominent relationship with sustainable behaviour in the literature [36,94]. The main demographic factors that have been found to affect behaviour according to Topal et al [93] are:…”
Section: Influential External Factors (Situational/contextual)mentioning
confidence: 99%
“…Based on the literature review conducted previously by Topal et al [31], it was revealed that the complexity of the urban sustainability behavior context required specification of variables that influence sustainability understanding and behavior. Moreover, it was necessary to specify the relationship between socio-psychological determinants of urban behavior in order to evaluate and analyze the individual practices (a determinant is defined herein as a factor that decisively affects the nature or outcome of something).…”
Section: Conceptual Approachmentioning
confidence: 99%
“…To analyze the relationship between this urban sustainability understanding and behavior and both influencing factors and personality traits The development process of the conceptual framework consists of four stages, which are presented in Figure 2. Topal et al [31] provided a systematic review of the influencing factors of urban sustainability behavior(s), fulfilling the requirements of stage 1. Topal et al [35] thereafter examined prominent environmental and sustainability behavior theories (stage 2), investigated socio-psychological determinants of urban sustainability understanding and behavior (stage 3), and synthesized these findings into a newly developed conceptual framework (stage 4), which has formed the basis for this current study.…”
mentioning
confidence: 99%
See 1 more Smart Citation